Evaluation of simulation learning materials use to fill the gap in Japanese dental English education - Seki, Naoko; Moross, Janelle; Sunaga, Masayo; Hobo, Koki; Miyoshi, Tomoe; Nitta, Hiroshi; Kinoshita, Atsuhiro; Morio, Ikuko (Journal of Medical and Dental Sciences, 2016)
Even though English is most frequently the common language when the patient's native language differs from that of a dentist, the opportunities for Japanese undergraduate dental students to learn dental English are now quite limited. The purposes of our study were to investigate: the effectiveness and feasibility of the computer-assisted simulation materials as one solution strategy for dental English education in Japan, and the needs and demands for dental English from the learners' side. Interactive simulation materials for medical interviews in English and clinical cases which were translated to English, were delivered via Learning Management System (LMS) to nineteen trainee residents of dentistry (residents). Evaluation for the materials, learners' knowledge and interests in the contents, and ease of operation were obtained by post-questionnaire (response rates were 100% and 95%, respectively). Both questionnaire-surveys received positive feedback toward the materials, yet 47% answered that they lacked the level of knowledge about contents of the medical interview in English. Results were sufficient to suggest that the residents would like to have the opportunity to study or practice medical interview in English, or English related to dentistry, and that the simulation materials could be one of the solution strategies for opportunity provision.